2000
DOI: 10.1346/ccmn.2000.0480205
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of Localized Crystallization of Halloysite and Kaolinite on Primary Minerals in the Weathering Profile of Granite

Abstract: Abstract~The formation of kaolin-group minerals in the weathering profile of granite, under the humid, temperate climate as found in Korea, was studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), and electron microprobe analysis (EMA). The granite was gradually weathered to saprolite. K-rich feldspar was not weathered in the profile, but plagioclase partially weathered to halloysite septa (i.e., wail-like masses). At the bottom of the profile, biotite had weathered to regularly interstratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 27 publications
1
15
1
1
Order By: Relevance
“…Because hornblende and plagioclase weather completely in the saprock layer , these minerals could contribute Al and Si to pore fluids in the saprock. Although some studies have linked halloysite formation to the weathering of K-feldspar (Jeong, 2000;Jeong and Kim, 2003;Papoulis et al, 2004), tubular halloysite was not observed on K-feldspar in our ESEM images and K-feldspar is a mineral with a smaller proportion (2%) in the quartz diorite than biotite (9%) . Our XRD results also are inconsistent with feldspar as the main source of halloysite formation because the secondary mineral peaks were stronger in saprolite, where biotite was the main mineral undergoing weathering.…”
Section: Discussion Bedrock Weathering and Secondary Mineral Formatiocontrasting
confidence: 66%
“…Because hornblende and plagioclase weather completely in the saprock layer , these minerals could contribute Al and Si to pore fluids in the saprock. Although some studies have linked halloysite formation to the weathering of K-feldspar (Jeong, 2000;Jeong and Kim, 2003;Papoulis et al, 2004), tubular halloysite was not observed on K-feldspar in our ESEM images and K-feldspar is a mineral with a smaller proportion (2%) in the quartz diorite than biotite (9%) . Our XRD results also are inconsistent with feldspar as the main source of halloysite formation because the secondary mineral peaks were stronger in saprolite, where biotite was the main mineral undergoing weathering.…”
Section: Discussion Bedrock Weathering and Secondary Mineral Formatiocontrasting
confidence: 66%
“…Islam and Lotse (1986) also observed a broad contribution to the diffraction curve, but they attributed it to randomly interstratified mica-chlorite. Halloysite is typically formed by weathering of volcanic ash materials, but it has also been reported in nonvolcanic environments ( Jeong, 2000). Taken together, the diffraction and the FT-IR data suggest that clay fractions of all soil samples contain some well crystallized clay types (illite and kaolinite) that probably originated from the soft parent rock as well as types that can be considered as decomposition products of the illite by preservation of the 2:1 layer structure (vermiculite/smectite and HIV/HIS) or by recrystallization (halloysite and gibbsite).…”
Section: Later) Thus If the Illite Contains 8% K 2 O (Fanmentioning
confidence: 99%
“…The SEM reveals that these clay minerals have an exfoliated "booklet-type" morphology ( Fig. 5f), which is commonly observed for kaolinite crystallizations in altered rocks (Jeong 2000;Papoulis et al 2004).…”
Section: Plagioclase Weathering Microsystemsmentioning
confidence: 77%